Prevalence of Urinary Incontinence among Pregnant Women of Multan City - Hira Iqbal, Saman Zafar, Nida Aslam, Namra Asif, Hafiz Muhammad Almas Sabir, Iqra Saleem, Nimra Sabir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Incontinence of urine (UI) is a type of lower urinary tract dysfunction that can occur when the natural urination process is disrupted. During pregnancy, incontinence, particularly stress UI, is a common issue. Aim: To identifying the prevalence, factors associated, and the effects of UI throughout pregnancy on health-related QoL. Methods: A cross - sectional descriptive research was carried out. 220 pregnant women who were attending an outpatient clinic at one of the hospitals in Multan were included in the study. As a means of measuring the results, the ICIQ—International Consultation on Incontinence Questionnaire—was utilized. The Questionnaire was distributed among pregnant women, and researcher filled the questionnaire by asking questions to them according to their response. Results: UI was present in 48(21.81%) of the study population. According to a frequency distribution analysis of urine incontinence in females, those b/w 29& 28 years of age, who have a B.M.I of range 18. 5 to 24.9 kg/m2 exhibit the most severe incontinence. Chi square test showed that p value is below 0.05 and study concluded that there is a statistically significant association between urinary incontinence and gravida, as well as between urinary incontinence and trimester.Understanding the prevalence of this condition can help healthcare providers to identify the risk factors associated with urinary incontinence in pregnant women and develop targeted interventions to prevent or manage the condition. Conclusion: UI occurs frequently in expectant mothers.Study concluded that there is a statistically significant association between urinary incontinence and gravida, as well as between urinary incontinence and trimester, among pregnant women in Multan CityA higher risk of UI throughout pregnancy was linked to age, the week of gestation & parity. Keywords: Pregnancy; Prevalence; Quality of life; Urinary incontinence